The Practice of Hilah in Contemporary Islamic Transactions and Finance: Between Legal Engineering and Sharia Objectives - Sunaryo, Agus; Zain, Muhammad Fuad; Rajafi, Ahmad; Zein, Anwar (Universitas Islam Sultan Agung, 2025)
Hilah is one of the essential concepts in the corpus of Islamic law, referring to a legal strategy employed to circumvent specific prohibitions without explicitly violating the textual provisions (nash). In the contemporary context, particularly within Islamic commercial law and modern Islamic finance, the concept of hilah has been extensively applied in financial products such as murabahah, tawarruq, and ijarah muntahiyah bi al-tamlik. This article aims to critically examine the implementation of hilah in modern Islamic economic practices and assess its alignment with maqashid sharia. The research adopts a normative juridical approach, employing content analysis of classical fiqh literature, contemporary fatwas issued by authoritative bodies such as the National Sharia Council-Indonesian Ulema Council and the Accounting and Auditing Organizations for Islamic Financial Institutions (AAOIFI), along with case studies from Islamic financial institutions. The findings reveal that although hilah may serve as a flexible legal instrument that offers certain benefits (maslahah) under specific circumstances, its manipulative use, particularly when driven solely by economic gain, can undermine the integrity and spirit of Islamic law. In practice, excessive reliance on hilah risks disguising forms of usury and compromising core principles of Islamic finance, such as justice, transparency, and protection for vulnerable parties. Therefore, strengthening regulatory and ethical frameworks in the development of Islamic financial products is imperative. Emphasis must be placed on a maqashid-oriented approach in assessing the validity of contracts, considering both formal legal compliance and substantive ethical and economic impact. This article recommends formulating fatwa guidelines grounded in maqashid and enhancing sharia literacy among practitioners in Islamic finance.